A soft phosphorus atom to "harden" an erbium(iii) single-ion magnet. Issue 38 (15th August 2018) - Chen, Shi-Ming; Xiong, Jin; Zhang, Yi-Quan; Yuan, Qiong; Wang, Bing-Wu; Gao, Song
Abstract : A single-ion magnet (Dsp)Er(COT) was obtained by replacing a carbon atom of [Cp*] − in (Cp*)Er(COT) by a soft P atom. Both relaxation barrier and blocking temperature are improved. Abstract : Beyond the lanthanide organometallic single-ion magnet (SIM) (Cp*)Er(COT) 1 ([Cp*] − = pentamethylcyclopentadienide; COT 2− = cyclooctatetraenide) that has a good performance, we managed to replace one coordinated carbon atom on the [Cp*] − ring by a soft phosphorus atom and obtained (Dsp)Er(COT) (CCDC No. ;1835955 ; Dsp − = 3, 4-dimethyl-2, 5-bis(trimethylsilyl)phospholyl) whose sandwich structure is reported here for the first time. This substitution results in a remarkable change of magnetic dynamics. It exhibits slow magnetic relaxation under a zero applied direct current (DC) magnetic field with an energy barrier (Δ/ k B ) of 358 K and magnetic hysteresis up to 9 K, both of which are higher than those of (Cp*)Er(COT). With the descended local symmetry of (Dsp)Er(COT), the energy barrier and blocking temperature ( T B ) both improve unexpectedly and are among the highest ones in Er(iii )-based single-molecule magnets (SMMs).